Analisis Manajemen Kurikulum Dalam Pelaksanaan Mutu Pendidikan Pada Program Studi Sastra Inggris di Fakultas Sastra Universitas Islam Sumatera Utara - Amna Apriany Delima Batubara; Suhati Suhati; Syaiful Bahri (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2021)
This research aims to obtain and determine the concept of English Literature at The Faculty Literature Islamic University of North Sumatera. This study uses a qualitative approach, naturalistic and triangulation techniques. The data collection techniques are using observation, interviews and documentation. The purpose of this research is to know and understand the concepts of the English Literature study program curriculum at the Faculty of Letters, Islamic University of North Sumatra. The results of the study showed that in the planning section it was seen from the readiness of the lecturer in providing a special time to make lectures by achieving the number of semester credits. In addition lecturers have the ability to predict the readiness of students in completing courses per semester. The planning of making English literature curriculum is in line with the output that will be produced by English literature study programs. In implementing the curriculum that is realized in the lecture process, the lecturers will adjust the face-to-face hours to what will be achieved by students at the end of the lecture, making Semester learning plans, giving their own space to lecturers in providing appropriate media selection courses to help students quickly understand material precisely. In addition, lecturers are able to realize the total number of Semester Credit System by adjusting the number of student attendance. Meanwhile the Evaluation section is also to give freedom to lecturers. To work more wisely and in applying and implementing policies during the lecture process.